Too Fine to be Good? Issues of Granularity, Uniformity and Error in Spatial Crime Analysis - Ramos, Rafael G. (Journal of quantitative criminology, 2021)
Crime counts are sensitive to granularity choice. There is an increasing interest in analyzing crime at very fine granularities, such as street segments, with one of the reasons being that coarse granularities mask hot spots of crime. However, if granularities are too fine, counts may become unstable and unrepresentative. In this paper, we develop a method for determining a granularity that provides a compromise between these two criteria.